Working Conditions in Hospitals before and during the COVID-19 Pandemic in Doctors' Assessments on the example of Slovakia - Sergej VOJTOVIC; Emilia KRAJNAKOVA (Communications of International Proceedings, 2022)
The COVID-19 pandemic affected not only the organization and management of healthcare facilities, but also the working conditions of healthcare workers. Changes in the working conditions of healthcare workers during the COVID-19 Pandemic have been the subject of several analyzes and investigations. At the same time, less attention is paid to how health workers themselves evaluate changes in working conditions during the pandemic, which has an impact on several aspects of their work and work performance. Therefore, we determined the main goal of the work to find out how hospital doctors evaluate changes in working conditions during the COVID-19 pandemic compared to the pre-covid period. To realize this goal, we used the results and data of an empirical survey of doctors' evaluation of satisfaction with work in hospitals before the pandemic and evaluation of changes in working conditions under the influence of the pandemic based on a 5-point scale. The obtained data were aggregated into individual indices with a value from 1 to -1, the reliability of these indicators and the correlations between the analyzed variables were calculated. Finding out the degree of satisfaction with the working conditions of doctors in hospitals in the pre-pandemic period and their change in the direction of deterioration or improvement in the period of the pandemic is important for the psychological mood of doctors, their work performance, the quality of health care provision and their other decisions, such as applying for work in other sectors of health care, despite the shortage of doctors to retire or look for work abroad.
Keywords: Hospitals; doctors; job satisfaction; working conditions; COVID-19